The Greek Communities in the Balkans and Asia Minor and Their Theatrical Activity 1800-1922 - Stamatopoulou-Vasilakou, Chrysothemis (Études helléniques / Hellenic Studies, 2008)
The purpose of this article is the comprehensive examination of theatre life in the economically robust Greek paroikies of Asia Minor, during the Ottoman Empire until the Asia Minor Catastrophe, as well as of the Balkan Peninsula. Special emphasis is given to the study of Greek theatre in Constantinople and Smyrna, on the one hand, because of the large Greek Orthodox populations in these significant large cities which were also business centres and major ports on the Mediterranean Sea, and, on the other hand, because of the wealth of information provided in the existing bibliographical sources. In contrast, reference to the theatre life of the Greeks in Bulgaria and Romania, because of the limited up-to-date relevant bibliography, is more restricted. In parallel with the historical events of the time, consideration is given to the rising and declining course of Greek theatre activity in these areas, as well as to its contributing factors: professional and amateur companies, actors, playwrights, translators and intellectuals.